PENGARUH MATA KULIAH KEWIRAUSAHAAN DAN PELATIHAN WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA EKONOMI KREATIF PADA MAHASISWA UNIVERSITAS ISLAM OKI (UNISKI) KAYUGUNG - Fernandes, Ari (MOTIVASI: Jurnal Manajemen dan Bisnis, 2020)
Purpose - This research was conducted on students of FKIP Islamic University OKI (UNISKI) Kayuagung. Unicorn students are required to take entrepreneurship courses and almost all attend creative entrepreneurship training that is regularly held. This research will answer the question whether the provision of courses and training can increase their entrepreneurial interest in the creative economyStock Exchange.Design/methodology  - The  sample  of this study  consisted  of  100students from Fikip Unsiki who were taken at random. The regression model of this study is: Yi = a + b1X1 + b2X2Where :Yi is interested in being a creative entrepreneur. i is an indicator of creative entrepreneurial interest. Namely: 1. The desire to work independently,2. The desire to obtain challenges, 3. The desire to obtain a fluctuating income and not small but stable, and 4. The desire to create something new. Each indicator is given a value on a scale of 5.Findings - The test results show that: 1) Entrepreneurship courses have a positive effect on the creative entrepreneurial interests of Islamic University OKI students. 2) Entrepreneurship training has a positive effect on UNISKI students' creative entrepreneurialinterests.  Design/methodology  - The  sample  of this study  consisted  of  100students from Fikip Unsiki who were taken at random. The regression model of this study is: Yi = a + b1X1 + b2X2Where :Yi is interested in being a creative entrepreneur. i is an indicator of creative entrepreneurialinterest.Namely:1.Thedesiretoworkindependently,2. The desire to obtain challenges, 3. The desire to obtain a fluctuating income and not small but stable, and 4. The desire to create something new. Each indicator is given a value on a scale of 5.Findings - The test results show that: 1) Entrepreneurship courses have a positive effect on the creative entrepreneurial interests of Islamic University OKI students. 2) Entrepreneurship training has a positive effect on UNISKI students' creative entrepreneurialinterests Purpose - This research was conducted on students of FKIP Islamic University OKI (UNISKI) Kayuagung. Unicorn students are required to take entrepreneurship courses and almost all attend creative entrepreneurship training that is regularly held. This research will answer the question whether the provision of courses and training can increase their entrepreneurial interest in the creative economyStock Exchange.